Carmen Miranda: an Embodied Marketplace Icon - Couto de Azevedo de Oliveira, Renata (Organizações & Sociedade, 2022)
Building upon the CCT framework of incorporation of ideologies, taste regimes, and national and regional interests by consumer cultures, this paper proposes that social and political ideologies are also embodied in marketplace icons. This paper aims, then, to bring together the concepts of iconicity and liminality to provide an account of Carmen Miranda as a marketplace icon who not only embodied the national myths of her time but also continues to be employed in the current marketplace for a variety of purposes. As such, icons like Carmen contribute to the production of marketplaces in which historical, political, and ideological issues are naturalized. Carmen’s collaboration via cultural industries such as radio and cinema, her omnipresence in advertising campaigns and in the printed media, and her influence on female fashion contributed to the consumer culture of her time. Moreover, the mythical character of her persona and her cultural legacy hold an expressive symbolic power, making her a remarkable contemporary marketplace icon. The key to her iconicity is her liminality; unsettling hierarchies, traversing social planes, and questioning identity. As a marketplace icon, Carmen’s legacy is thus constantly reissued, founded upon the ambivalence of her persona and signaling her transgressive potential.